What's new in nasoalveolar molding technique: A current literature review - Rathburn Tyler; McLagan Raymond; Amara Abreu; Levy-Bercowski Daniel (Dentistry Review, 2023)
Objective: The aim of this study was to review and summarize the effects of nasoalveolar molding (NAM) therapy published in the most recent literature. Method: A search were conducted from “nasoalveolar molding,” “nasoalveolar molding Grayson,” and “nasolabial esthetics”. The articles were then subdivided into case reports, editorials/expert opinions, and traditional prospective and retrospective studies Results: In order to summarize the results of the literature review, the discussion section was organized into three primary categories. The first of these categories deals with the burden of treatment to the NAM patient and the caregiver, the psychological and monetary effect on the caregiver(s), and the effect of NAM treatment on the number of surgeries required. The second category deals primarily with the specific treatment effects seen as a result of NAM therapy, such as the improvement of nasal symmetry and lengthening of the columella, as well as studies that compare NAM treated patients to non-NAM treated and normal controls. Lastly, we have included a brief summary of alternative methods to NAM therapy, including the recent use of CAD/CAM technology in NAM therapy. Conclusions: Based on the current literature, NAM does indeed show significant improvements in nasolabial esthetics and increases columellar length. It is shown to have positive psychosocial outcomes and lower cost for caregivers via reduction of future surgeries. Finally, technological advancements are allowing for streamlined NAM fabrication.